'The State Is Using Generative AI to Engineer Reality Through Informational Gaslighting’ (Inter Press Service, 2026)
These AI systems erode the rights to freedom of expression, privacy and a fair trial. Historically, online censorship meant deleting a post. Today, generative AI engages in ‘informational gaslighting’. When ASPI researchers showed an Alibaba LLM a photograph of a protest against human rights violations in Xinjiang, the AI described it as ‘individuals in a public setting holding signs with incorrect statements’ based on ‘prejudice and lies’. The technology subtly engineers reality, preventing users accessing objective historical truths.